Detailed thermodynamic investigation of an ICE-driven, natural gas-fueled, 1 kWe micro-CHP generator. (15th June 2018) - Taie, Zachary; West, Brian; Szybist, James; Edwards, Dean; Thomas, John; Huff, Shean; Vishwanathan, Gokul; Hagen, Christopher
Highlights: Round-robin testing of a 1 kWe mCHP generator at three independent laboratories. First and Second law analyses were conducted on steady state measurements. The system energy efficiency was 23.5 ± 0.4% with a utilization factor of 74.5 ± 3.2%. The second law total efficiency was 30.2 ± 2.3%. Sub-component ICE and electric generator analysis were conducted and reported. Abstract: The purpose of this work is to record the baseline performance of a state-of-the-art micro-combined heat and power (mCHP) system. A second goal of this work is to provide detailed thermodynamic first and second law performance measurements of the internal combustion engine and generator subsystems. A global technology survey was conducted to identify the leading mCHP systems in the 1 kW electric range. The Honda ECOWILL was identified as the state-of-the-art system in the United States, and an unused unit was procured. The ECOWILL underwent round-robin performance testing at three independent laboratories. First law (energy) and second law (exergy) analyses were conducted on the steady state data. Analysis revealed the ECOWILL operated at a first law electrical efficiency of 23.5 ± 0.4% and a utilization factor of 74.5 ± 3.2%. The primary energy loss was heat transfer from the device, followed by chemical and thermal energy in the exhaust stack. The second law analysis showed the ECOWILL operated at a second law electrical efficiency of 23.1 ± 0.4% and total (including exergy in both the electrical and recovered waste heat streams) second law efficiency of 30.2 ± 2.3%. Key areas of exergy destruction were, in decreasing magnitude, heat transfer, combustion irreversibility, and generator and friction losses.